1992
DOI: 10.1209/0295-5075/17/6/010
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Phase Diagram and Scaling Relations for Stationary Diffusional Growth

Abstract: We propose a phase diagram for the selection of growth patterns in systems with a conserved quantity which evolve at asymptotically constant growth rate. The occurrence of different growth forms like fractal, compact or dendritic, and the various transitions between them are characterized by scaling relations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(79 citation statements)
references
References 18 publications
8
71
0
Order By: Relevance
“…It is observed that the top surface of the lamellar crystal is also undulated a few nm in height as indicated by the radial stripes. In films thinner than 15nm, the crystal morphology changes to that observed in the diffusion-controlled growth [6], as shown in Fig.1 b to f. In 14 nm thick films, the crystal shows the splitting of growth face to have many irregular branches typical in the dense branching morphology (DBM) or compact seaweed (CS) [11,12] . The envelope of this branching structure is nearly circular; we call hereafter this envelope "average front" in contrast to the local growth interface of its branch [13].…”
Section: Resultsmentioning
confidence: 86%
“…It is observed that the top surface of the lamellar crystal is also undulated a few nm in height as indicated by the radial stripes. In films thinner than 15nm, the crystal morphology changes to that observed in the diffusion-controlled growth [6], as shown in Fig.1 b to f. In 14 nm thick films, the crystal shows the splitting of growth face to have many irregular branches typical in the dense branching morphology (DBM) or compact seaweed (CS) [11,12] . The envelope of this branching structure is nearly circular; we call hereafter this envelope "average front" in contrast to the local growth interface of its branch [13].…”
Section: Resultsmentioning
confidence: 86%
“…It is important to note that eq 3, with the boundary conditions at the interface given by eqs 1 and 4, is similar to the equation used by Müller-Krumbhaar and collaborators [10][11][12][13][14][15] 20 That is, if eq 1 would be written as…”
Section: Resultsmentioning
confidence: 98%
“…Apparently, we have lost the general picture given by the diffusional model proposing the existence of a diffusion zone, which with eq 7 and the boundary conditions given by eqs 1 and 2, successfully explains the pattern formation and the morphology evolution in LMs. 27,28 In the same way, apparently, we have also lost the connection with the morphology diagram with regions of different morphological structures, [6][7][8][9][10][11] determined by the control parameters ∆ and ε, as explained above. Here, we will assess in what conditions the 2D hydrodynamic eq 4 can recover that picture related to pattern formation and to the morphology diagram.…”
Section: Morphology Evolution In Langmuirmentioning
confidence: 99%